Continued gefitinib retreatment beyond progression in patients with advanced non-small cell lung cancer harboring sensitive EGFR mutations. Issue 10 (October 2020) - Jiang, Xuhong; Li, Xiaoqing; Tu, Lingli; Cai, Jin; Wei, Man; Wu, Zhongjun; Sun, Lan
Purpose: To evaluate the effectiveness and safety of gefitinib retreatment beyond disease progression in patients with advanced non-small cell lung cancer (NSCLC) with sensitive epidermal growth factor receptor ( EGFR ) mutations. Methods: Data from patients with stage III/IV NSCLC were analyzed retrospectively. Patients with sensitive EGFR mutations received first-line treatment with gefitinib followed by retreatment with gefitinib after disease progression. Progression-free survival (PFS) after the first treatment (PFS-1) was defined as the time to progression or death using the Response Evaluation Criteria in Solid Tumors criteria (RECIST) v1.1 criteria. The second PFS (PFS-2) was defined as the interval between the first and second progressions, at the investigator's discretion. Toxicities were recorded in accordance with the National Cancer Institute (NCI)-Common Terminology Criteria (CTC) version 4.0. Results: Sixteen patients aged 53 to 80 years (median 66 years) were included in the analysis. The median PFS-1 and PFS-2 were 10.0 months and 14.0 months, respectively. The median overall survival (OS) was 36.0 months. No toxicity of grade 3 or worse was observed. Conclusions: Our findings suggest that gefitinib retreatment beyond disease progression may be an effective and tolerable approach for NSCLC patients with sensitive EGFR mutations.